In vitro plant regeneration of Iraqi cotton (Gossypium hirsutum L.) cultivars through embryonic axis - Hussein Abdullah Ahmed; Mortaza Hajyzadeh; Surendra Barpete; Sebahattin Ozcan (مجلة مركز بحوث التقنيات الاحيائية, 2014)
In plant tissue culture studies, obtaining new plantlets from different parts of plant is a very important feature with direct or indirect ways of regeneration. The plant show different regeneration capacities from species to species. In this present study, in-vitro direct shoots development from embryonic axis of cotton (Gossypium hirsutum L. cv. Lashata) were comparatively studied. Embryonic axis, embryonic hypocotyl and plumule obtained from five days old in-vitro grown seeds. All explants were cultured on MS media supplemented with 1- 4 mg/l Benzyl amino purine (BAP) + 0.1 mg/l Naphthalene acetic acid (NAA) and 3 mg/l activated charcoal. Cultured explants were kept at growth chamber with photoperiod for 16 hours light and 8 hours dark, at 25oC. Reproducible in-vitro plant regeneration was obtained from embryonic axis when cultured onto MS medium supplemented 1 mg/l BAP + 0.1 mg/l NAA and 3 g/l Activated charcoal. Shoot induction was to be noted 53.3%, 36.7% and 12.3 in embryonic axis, plumule and embryonic hypocotyl respectively. All these shoots were capable of rooting on MS medium supplemented with 0.1 mg/l NAA, and establishing in soil 3-4 weeks.